The Effect of Excellent Services and Corporate Images to Customer Satisfaction on Financial Banking Sectors - Vivin Hanitha (Komunitas Dosen Indonesia, 2020)
The banking sector plays an important role in the world economy. In a very tight banking competition, banks must be able to understand what they want and what is needed by their customers. And then the bank must be able to create banking products that are suitable and can satisfy the needs of its customers. Customer satisfaction can form a positive perception and can further position the company's image in the minds of customers. Excellent service that is doing the best possible service to customers or consumers, causing satisfaction. The purpose of excellent service is to provide services so that they can meet and satisfy customers so that the company gets maximum profit.